Emergency Notification System for the Detection of Falling, Car Accident and Heart Rate Failure Using Smart phone and Smart watch. - Hamid M. Ali; Ali M. Muslim (Journal of Madenat Alelem University College, 2017)
There are a lot of people facing a problem of unexpected death or health damage due to the lack of medical care at the right time, especially elderly people, patient with disabilities and people that are living alone who are required to be continuously under surveillance for the purpose of safety and emergency response. As the smartphone becomes an integrated part of human daily life which has the ability of complex computation, internet connection and also contains large number of hardware sensors, encourage implementation of the proposed system based on smartphone to be utilized in the public healthcare. Most of the works done in this field imposed the restriction of fixing the smartphone in certain position on human body to easy infer the emergence case from the data of the smartphone sensors. To overcome this restriction, the proposed system incorporated a smartwatch, together with smartphone freely carried by the user, for better performance results. The use of smartwatch assisted in providing distinct separable signal variation from the smartwatch accelerometer and gyroscope sensors to recognize emergency case such as falling, car accident and heart rate failure. Immediately after cases that are mentioned previously the proposed systems ends details information such as videos, location, heart rate etc. to the emergency center and emergency contact to provide help at the right time. The system was practically tested in real simulated environment and achieved quite very good performance results